Functions of GSK-3 Signaling in Development of the Nervous System - Kim, Woo-Yang; Snider, William D. (Frontiers in Molecular Neuroscience, 2011)
GSK-3 is central to multiple intracellular pathways including those activated by Wnt/beta-catenin, Sonic Hedgehog, Notch, growth factor/RTK, and G protein-coupled receptor signals. All of these signals importantly contribute to neural development. Early attention on GSK-3 signaling in neural development centered on the regulation of neuronal polarity using in vitro paradigms. However, recent creation of appropriate genetic models has demonstrated the importance of GSK-3 to multiple aspects of neural development including neural progenitor self-renewal, neurogenesis, neuronal migration, neural differentiation, and synaptic development.